Post-Cognitivism and the Indissoluble Bonding of Languaging, Embodiment, and Thinking - Batisti, Filippo; Vidal, Marcos G. (JoLMA)
Classical cognitive science often strips the inherent social character out of language, treating it as a system of internal mental representations, and so does Generative Linguistics. In contrast, post-cognitivist approaches to psychology reject representationalism but struggle with language’s capacity to refer beyond sensory experience. Cognitive Linguistics addresses meaning and embodiment but remains somewhat isolated from broader post-cognitivist thought. The enactive approach overtly problematizes the concept of representation, but tends to marginalize language; when such focus is taken, a coherent account of semantic content remains an unresolved task. This paper surveys philosophical and linguistic perspectives on language within post-cognitivist frameworks and proposes a blueprint for future research based on four points: sociality and interaction, embodiment, ecological validity, and representation-as-praxis.